(untitled) (Global Journal of Management and Business Research, 2023)
The purpose of this study is to look at the relationship between intrapreneurship dimensions and organizational factors as well as the effects they can have on the performance of Palestinian banks in the West Bank Furthermore this research concentrated on both financial and non-financial performance Based on data collected from 7 West Bank Palestinian banks and 344 individual replies preliminary findings revealed that intrapreneurship dimensions have statistically significant effects on organizational performance to diverse degrees and at varying impact strengths Proactiveness innovation and offensive competitiveness appeared to be the most influential dimensions Furthermore organizational factors moderate the association between intrapreneurship and organizational success while also having a considerable beneficial impact on organizational performance